The failures of horizontal accountability at the subnational level: a perspective from the Global South. Issue 5 (3rd July 2020) - de Almeida Lopes Fernandes, Gustavo Andrey; Teixeira, Marco Antonio Carvalho; Fernandes, Ivan Filipe de Almeida Lopes; Angélico, Fabiano
ABSTRACT: In new democracies, horizontal accountability tends to be more fragile than vertical since authoritarian institutional legacies are more difficult to transform than organising free and fair elections. These barriers to full democratisation are stronger at subnational levels, where local old authoritarian elites are better able to hold institutional power and block transformations. This viewpoint presents data from Brazil, one of the strongest democracies of the Global South. After three decades of free elections, the design of oversight institutions of Brazilian subnational governments has hardly changed from dictatorial periods, leading to administrative practices and routines that undermine the transparency of monitoring and assessing public policy. Using institutional and behavioural measures of transparency, it shows that there are important bottlenecks to adequate accountability in Brazil.